KESESUAIAN PENGAJARAN SASTRA DALAM BUKU TEKS KELAS X KURIKULUM 2013 MENUJU ABAD 21: PERSPEKTIF PENGAJARAN SASTRA MOODY - Rudi Umar Susanto (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
In applying the principles of learning implementation in the perspective of literature appreciation, the principles in literaturelearning have a purpose as a means of increasing sensitivity to love for the culture of the Indonesian nation. In addition, literature learning can provide spiritual satisfaction and understanding in language. Literaturelearning is not merely a lesson of history, flow, and literature theory but the implementation of all these elements. Broadly speaking, the focus in literature learning can be seen through two aspects. This will give an idea as to what forms of literature appreciation learning in the present. This focus can be seen in general and implementation at the curriculum level in each school. In general, the purpose of learning in the perspective of literature aims for students to gain new experiences in enjoying a literature work and obtain knowledge in a literature work. Literaturework is an embodiment of the essence of a reality that is inscribed in a work. This paper explores the correlation between the relationship of  literature teaching in class X curriculum textbook 2013 to the 21st century: perspective of moody literature teaching. In addition, there is a readiness in covering a weakness in every implementation of literature and language learning. In the implementation in the world of education, especially language and literature learning in the current era of globalization, the need for signs or rules to apply the appropriate rules, this aims as a concern for every teacher